The Effect Of Leadership Style, Organizational Climate, And Academic Supervision On The Performance Of State Elementary School Teachers In Sumowono District, Semarang Regency - Diah Rahayu, Septaria; Kusumaningsih, Widya; Sulianto, Joko (Advances In Social Humanities Research, 2024)
The purpose of this study is to: 1) determine and analyze the influence of leadership style on teacher performance. 2) determine and analyze the influence of organizational climate on teacher performance. 3) determine and analyze academic supervision on teacher performance. 4) determine and analyze the influence of leadership style, organizational climate, and academic supervision on teacher performance. The research approach used is quantitative. This type of research uses correlational research. The population of this study was 202 teachers and the research sample was 134 teachers. Data collection was carried out using a questionnaire. The data analysis technique used in this study was descriptive data analysis, prerequisite tests including normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests and hypothesis tests including simple and multiple linear regression. The results showed that: 1) the correlation between leadership style and teacher performance was 0.938. the influence of leadership style on teacher performance was 88.0%, 2) the correlation between organizational climate and teacher performance was 0.858. the influence of organizational climate on teacher performance is 73.6%, 3) the correlation between academic supervision on teacher performance is 0.798. the influence of academic supervision on teacher performance is 63.8%, 4) the correlation between leadership style, organizational climate, and academic supervision on teacher performance is 0.905. the influence of leadership style, organizational climate, and academic supervision on teacher performance is 90.5%. The conclusion of this study is that leadership style, organizational climate, and academic supervision on teacher performance are 0.905 or 90.5 % . The author suggests that teachers evaluate and develop learning, then teachers can also attend training and seminars in order to improve teacher performance